2002
DOI: 10.1093/ajcn/75.6.1084
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effect of including egg yolk in the weaning diet of breast-fed and formula-fed infants: a randomized controlled trial

Abstract: n-3 Fatty acid-enriched eggs may provide a means of increasing dietary DHA during the second 6 mo of life. Egg yolks may also be a useful source of iron during the weaning period and can be safely included in the weaning diet with no perturbations in plasma cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 22 publications
5
55
0
Order By: Relevance
“…The "n-3PUFA-status" in Danish infants also seems to be more favorable compared with other populations. The n-3LCPUFA content of RBC at 12 mo in our unsupplemented group (24) was comparable with the levels found in the groups supplemented with DHA-enriched eggs in two studies from the United States and Australia (31,32). Thus, we would expect that the results we report here would be stronger in infants from countries with a lower fish intake.…”
Section: Discussionsupporting
confidence: 87%
“…The "n-3PUFA-status" in Danish infants also seems to be more favorable compared with other populations. The n-3LCPUFA content of RBC at 12 mo in our unsupplemented group (24) was comparable with the levels found in the groups supplemented with DHA-enriched eggs in two studies from the United States and Australia (31,32). Thus, we would expect that the results we report here would be stronger in infants from countries with a lower fish intake.…”
Section: Discussionsupporting
confidence: 87%
“…It is therefore surprising that only few studies tried to optimise DHA status via complementary feeding [13][14][15]21]. Most of these studies examined effects of preformed DHA either by enriched egg yolk [13,14] or by fish oil [15].…”
Section: Discussionmentioning
confidence: 99%
“…Two dietary intervention studies showed that provision of n-3 LC-PUFA-enriched egg yolk resulted in higher values of erythrocyte membrane DHA (RBC-DHA) compared to control groups [13,14]. Damsgaard and colleagues found fish-oil supplementation from age 9-12 months to increase RBC-DHA levels relative to controls [15].…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of meat increased AA concentration in the blood of formula-fed but not of breastfed infants (Luukkainen et al, 1996), whereas consumption of egg yolk increased the DHA concentration (Makrides et al, 2002;Hoffman et al, 2004). LC-PUFA status was significantly higher when LC-PUFAs were supplemented than without supplementation (Carnielli et al, 2007), and resulted in earlier sitting without help at the end of the first year of life (Agostoni et al, 2009).…”
Section: Discussionmentioning
confidence: 99%